The impact of heterotopic ovarian tissue transplantation with varied volumes on reproductive endocrine function in oophorectomized rats - Nana Tian; Chunhui Liu; Zhihui Cai; Junrong Shi; Pin Li; Shasha Bai; Xiaoxin Du; Gaoyuan Liu; Min Geng; Peishan Weng (Taylor & Francis Group, 2024)
Background This study aimed to investigate the effects of different volumes of ovarian tissue transplantation on the reproductive endocrine function of rats after oophorectomy.Methods Female rats were selected to establish a castration model and then underwent different volumes of ovarian tissue transplantation. Group I served as the sham operation group. The transplantation group was divided into five subgroups based on the calculated ratio of ovarian weight to body weight in normal female rats, δ = (2.52 ± 0.17) ×10−4: Group II: transplanted ovarian volume was δ; Group III: 0.75δ; Group IV: 0.5δ; Group V: 0.25δ; Group VI: without ovarian transplantation. The post-transplant oestrous cycle recovery was observed, and blood samples were collected every 2 weeks to measure serum hormone levels. Histological evaluation was performed at the end of the observation period.Results Rats in Group V exhibited disrupted oestrous cycles after transplantation, which were significantly longer than those in Group I. Rats in Groups II, III, and IV showed no cyclic changes. At 6 weeks post-transplantation, rats in Group V had lower E2 and AMH levels and higher FSH levels compared to Group I. The uterine wet weight and the number of normal follicles in Group V were significantly lower than those in Group I, but the number of atretic follicles was higher than in Group I.Conclusion The larger ovarian tissue transplantation resulted in a faster recovery with a higher survival rate of the uterus and normal follicles, compared to smaller ovarian tissue transplantation.